From subenca to ba fenecer. Demanding Ensenada’s Cadastre for the Study of Modern Galician Language - Vidal Fonseca, Guillermo (Madrygal. Revista de Estudios Gallegos, 2021)
The studies of Galician historical linguistic always faced difficulties for their investigations on early modern period Galician language due to the shortage or less proliferation of written sources in this language during this period in comparison with the previous or the subsequent ones. Through the study of several documents about Ensenada’s Cadastre, developed in Spanish on the 18th century, concerning the Galician region of Barcala, we identify through an exhaustive personalised investigation more than half a hundred voices or constructions clearly Galician ‒or affected by typical phenomena of the Galician of that era‒ that we analyse in detail in different grammatical levels: phonetic, morphologic, syntactic, lexical and semantic. The study of those interferences of Galician language in Spanish language in texts, allows us to approach different characteristics of average Galician, particularly the one spoken in that western Galician region and, through that contribution, the article expects to claim and to point out the value of a necessity still unexploited: to take advantage of Ensenada’s Cadastre as an indirect documental source to study modern Galician language, in spite of being written in Spanish.